New gold(I) and gold(III) coordination complexes derived from N and S heterocycles - Kifle Hagos, Tesfamariam (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2006.